Books and their Users: Socio-Cultural and Linguistic Aspects in an Engineering School - Rousseau, Ronald; Andegehuchte, Patrick V. (Journal of Information and Knowledge, 1995)
In this article the use of borrowable books in the library of a Aemish engineering school is examined. In particular, we examine the significance of the publication date and of the language on loans. First, loan figures of one year are compared with figures of other libraries. The collection has been divided into ten subfields according to the subject. Note worthy differences between these subfields are explained, when possible. Next, the age distribution of available and of borrowed books is given. They clearly illustrate that loans of recent books largely exceed loans of older ones. The availability and use of the books according to their language is thoroughly discussed, because this is certainly relevant in a multilingual country. Users mostly borrow books in their mother tongue (Dutch), but English is preferred far above French and German. Nevertheless, availability and number of borrowings vary considerably per subfield. This study is aimed at an improvement of users’ satisfaction, an augmentation of the collection’s borrowing rate and the development of better criteria for collection management.